USE OF SEWAGE SLUDGE AND PALM HEARTH RESIDUE OF Lantana camara SEEDLINGS PRODUCTION - Barone, E. P.; Silva, F. A. M.; Ferraz, M. V. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The sewage sludge use in agriculture has been increasingly promising, especially with regard to the cultivation of forest and ornamental plants. The objective of this study was to evaluate the Lantana camara viability seedlings, an ornamental plant widely produced in the Vale do Ribeira - São Paulo - Brazil, using sewage sludge composted with peach palm, lime sludge, or in combination with other structural components, such as cattle manure, soil and peel of charred rice. For this, 8 treatments (different substrates) were formulated with 4 replicates, each one composed of 15 seedlings in a completely randomized design (CRD). The chemical and physical composition of the substrates, as well as the dry mass of shoot and dry mass of root, and macronutrient contents in the dry mass of shoot were evaluated. Among the materials tested for the production of L. camara seedlings it is advisable to use substrate to the base composed of sewage sludge and peach palm (Bactris gasipaes Kunth), without addition of other materials. The substrate widely used by producers in the region presented problems from the physical and chemical point of view. The sludge sewage sludge cannot be used in the composition of substrates due to excess salts and high alkalinity.